Autologous serum skin test in chronic idiopathic urticaria: Prevalence, correlation and clinical implications - Kanokvalai Kulthanan (2018)
Some cases of chronic idiopathic urticaria (CIU) have histamine-releasing IgG autoantibodies in their blood. This disease subgroup is called "autoimmune urticaria". To date, the autologous serum skin test (ASST) is the best in vivo clinical test for the detection of basophil histamine-releasing activity in vitro. This study aimed to find the prevalence of ASST positive cases in Thai patients with CIU, to identify factors related to the positivity of ASST and to find the clinical implications of ASST in CIU. A retrospective study was performed among 85 CIU patients who attended the Urticaria Clinic at the Department of Dermatology, Siriraj Hospital and were willing to perform ASST, from January 2002 to December 2003. Twenty-one (24.7%) patients had a positive ASST. There was no significant difference between patients with positive ASST and negative ASST as to the severity of the disease (wheal numbers, wheal size, itching scores and the extent of body involvement) as well as the duration of the disease.